Polymer membranes and their applications
By controlling the volume of the solid volume (Vmp) and the kurtosis (Sku) of the peak portion on the surface of the polymer film, the problems of polymer film stickiness and air residue are solved, and the preparation of laminated glass without bubble defects and good weather resistance is achieved.
Patent Information
- Application Number
- CN202210738983.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-06-28
AI Technical Summary
During the preparation of laminated glass, the polymer film is prone to sticking due to gravity and viscosity, which leads to difficulty in access or damage, and it is difficult to completely remove air residue, resulting in poor appearance and poor weather resistance.
By controlling the volume (Vmp) and kurtosis (Sku) of the peak portion surface within a specific range, severe stickiness and enhance the exhaust effect, thereby preparing laminated glass without bubble defects and good weather resistance.
The smoothness of polymer films during stacking and pre-compression is achieved, the amount of scrap of polymer films is reduced, and the weather resistance and appearance quality of laminated glass are improved.
Smart Images

Figure GHA0000006509580000251 
Figure GHA0000006509580000261 
Figure GHA0000006509580000262
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer film, in particular to a polymer film having a specific peak material volume (Vmp) and kurtosis (Sku) on its surface. The present invention also relates to a laminated glass made from the polymer film. Background Art
[0002] Laminated glass is a composite glass material that is formed by sandwiching a polymer film between two glass sheets and tightly combining the glass sheets and the polymer film by heat pressing. Laminated glass is widely used in the automotive and construction industries because of its better impact resistance and sound insulation.
[0003] Since the preparation process of laminated glass involves hot pressing between glass sheets and polymer films, in order to prevent air from remaining between the glass sheets and the polymer films of the laminated glass, patterns are usually embossed on the surface of the polymer film in advance to form patterns (i.e., a concave-convex structure is designed) so that the air can be discharged smoothly during the pre-pressing period, thereby preventing bubbles from existing in the laminated glass. In addition, during the preparation of laminated glass, the polymer film is first cut into the desired size, and the cut polymer films are stacked and placed for subsequent pressing processes. However, during the placement process, the polymer films may stick to each other due to the influence of gravity and polymer viscosity, resulting in difficulties in subsequent use of the polymer films, and even damage to the polymer films. In addition, during the preparation process of laminated glass, it is often difficult to fully remove the air remaining between the glass sheets and the polymer films of the laminated glass, resulting in poor appearance or poor weather resistance of the laminated glass. Summary of the invention
[0004] The inventors have found that the above problems can be unexpectedly solved by controlling the peak volume (Vmp) and kurtosis (Sku) on the surface of the polymer film. Therefore, the present invention relates to a polymer film with a specific peak volume and kurtosis. The polymer film of the present invention does not cause severe sticking and can pass the "self-adhesion test", and the laminated glass made using the polymer film of the present invention does not have bubble defects on the appearance. In a preferred embodiment of the present invention, the polymer film has excellent weather resistance (shown in the "high temperature bubble test" result herein).
[0005] Specifically, an object of the present invention is to provide a polymer film having a first surface and a second surface, wherein the first surface has a load area ratio of 10% and a thickness of 0.15 μm. 3 / μm 2 (cubic micrometers / square micrometers) to 1.20 μm 3 / μm 2The load area ratio, Vmp and Sku are defined in accordance with ISO 25178-2:2012.
[0006] In some embodiments of the present invention, the second surface has a load area ratio of 0.15 μm 3 / μm 2 Up to 1.20μm 3 / μm 2 , and a Vmp of 0.73 to 10.02, wherein the load area ratio, Vmp and Sku are defined according to ISO25178-2:2012.
[0007] In some embodiments of the present invention, the first surface and the second surface each independently have a mean width of profile elements (Rsm) of 10 μm to 660 μm, wherein the mean width of profile elements is defined according to ISO 4287:1997.
[0008] In some embodiments of the present invention, the glass transition temperature (Tg) of the polymer film is 5°C to 23°C.
[0009] In some embodiments of the present invention, the polymer film comprises polyvinylacetal.
[0010] In some embodiments of the present invention, the polyvinyl acetal can be selected from the group consisting of poly(vinyl formal), poly(vinyl acetal), poly(vinyl butyral), poly(vinyl valeral), poly(vinyl hexanal), and combinations thereof. In a preferred embodiment of the present invention, the polyvinyl acetal is poly(vinyl butyral).
[0011] In some embodiments of the present invention, the number average molecular weight (Mn) of the polyvinyl acetal is 90,000 to 120,000.
[0012] In some embodiments of the present invention, the polymer film further comprises a plasticizer.
[0013] In some embodiments of the present invention, based on 100 parts by weight of the polyvinyl acetal, the content of the plasticizer is 35 parts by weight to 50 parts by weight.
[0014] Another object of the present invention is to provide a laminated glass, comprising a first glass sheet, a second glass sheet, and an intermediate film located between the first glass sheet and the second glass sheet, wherein the intermediate film is provided by the polymer film as described above.
[0015] In order to make the above-mentioned objectives, technical features and advantages of the present invention more obvious and easy to understand, some specific implementation schemes are described in detail below. DETAILED DESCRIPTION
[0016] Some specific embodiments according to the present invention will be described in detail below; however, the present invention can also be practiced in a variety of different forms, and the protection scope of the present invention should not be limited to the specific embodiments.
[0017] Unless otherwise stated, the terms “a”, “an”, “the” and similar terms used in the specification and claims should be understood to include both the singular and the plural.
[0018] Unless otherwise specified, the terms “first”, “second” and the like used in the specification and the claims are merely used to distinguish the described elements or components and have no special meanings and are not used to represent a sequence.
[0019] Unless otherwise specified, in this specification and claims, the term "load area ratio" is defined in accordance with ISO 25178-2:2012. A load area curve is a function curve of the surface height to the area of the area it covers, and the load area ratio refers to the area above a specified height.
[0020] Unless otherwise specified, in this specification and claims, the term "peak volume (Vmp)" is defined in accordance with ISO 25178-2: 2012. Vmp is the volume of the reduced peak of a material at a specific loading area ratio.
[0021] Unless otherwise specified, in this specification and claims, the term "kurtosis (Sku)" is defined in accordance with ISO 25178-2:2012. Kurtosis refers to the sharpness of the surface height distribution of the roughness profile. When Sku is 3, the height distribution is normally distributed, with sharp and indented portions coexisting. When Sku is less than 3, it means that the height distribution is flat. When Sku is greater than 3, it means that the height distribution is spiked.
[0022] Unless otherwise specified, in this specification and claims, the term "mean length of profile curve elements (Rsm)" is defined in accordance with ISO 4287: 1997. Rsm is the mean length of profile curve elements over a reference length, representing the distance between embossed patterns.
[0023] The utility of the present invention compared with the prior art is to provide a polymer film having a specific peak volume (Vmp) and peak degree (Sku) that can effectively solve the sticking problem, and a laminated glass without bubble defects provided by the polymer film, preferably a laminated glass without bubble defects and good weather resistance provided by the polymer film. The polymer film of the present invention is particularly beneficial to the process smoothness of the laminated glass and can reduce the amount of polymer film scrapped. The following provides a detailed description of the polymer film of the present invention and its related applications.
[0024] 1. Polymer film
[0025] 1.1. Surface characteristics of polymer films
[0026] 1.1.1. Peak volume (Vmp) and kurtosis (Sku)
[0027] In the process of preparing laminated glass, considering the smoothness of the laminated glass process, the polymer film is usually cut into the same size as the glass sheet, and the cut polymer films are stacked and placed for the subsequent preparation of laminated glass. However, since the polymer itself has a certain viscosity, under the influence of gravity, adjacent polymer films will stick to each other. In addition, in order to allow the air to be discharged smoothly without remaining between the polymer film and the glass sheet (i.e., bubble defects), the surface of the polymer film needs to be formed with a embossed pattern (i.e., a specific concave-convex structure) to facilitate exhaust during the pre-pressing of the polymer film and the glass sheet. However, in the process of preparing laminated glass, it is often difficult to fully remove the air remaining between the glass sheet and the polymer film of the laminated glass, resulting in poor weather resistance of the laminated glass, and even bubble defects in the appearance when the preparation is completed. In this regard, the inventors have found that the above-mentioned adhesion problem and bubble defect problem can be solved by controlling the peak volume (Vmp) and peak degree (Sku) of the polymer film surface within a specific range, and the weather resistance of the laminated glass can be further improved. The Vmp and Sku are parameters related to surface roughness. For relevant descriptions of the Vmp and Sku parameters, please refer to ISO25178-2:2012, which is a measurement specification for evaluating surface morphology. The full text of the specification is incorporated herein for reference.
[0028] Specifically, the polymer film of the present invention has a first surface and a second surface, wherein the Vmp value of the first surface at a load area ratio of 10% is 0.15 μm 3 / μm 2To 1.20 μm 3 / μm 2 , for example, 0.15 μm 3 / μm 2 、0.16 μm 3 / μm 2 、0.17 μm 3 / μm 2 、0.18 μm 3 / μm 2 、0.19 μm 3 / μm 2 、0.20 μm 3 / μm 2 、0.21 μm 3 / μm 2 、0.22 μm 3 / μm 2 、0.23 μm 3 / μm 2 、0.24 μm 3 / μm 2 、0.25 μm 3 / μm 2 、0.26 μm 3 / μm 2 、0.27 μm 3 / μm 2 、0.28 μm 3 / μm 2 、0.29 μm 3 / μm 2 、0.30 μm 3 / μm 2 、0.31 μm 3 / μm 2 、0.32 μm 3 / μm 2 、0.33 μm 3 / μm 2 、0.34 μm 3 / μm 2 、0.35 μm 3 / μm 2 、0.36 μm 3 / μm 2 、0.37 μm 3 / μm 2 、0.38 μm 3 / μm 2 、0.39 μm 3 / μm 2 、0.40 μm 3 / μm 2 、0.41 μm 3 / μm2 、0.42μm 3 / μm 2 、0.43μm 3 / μm 2 、0.44μm 3 / μm 2 、0.45μm 3 / μm 2 、0.46μm 3 / μm 2 、0.47μm 3 / μm 2 、0.48μm 3 / μm 2 、0.49μm 3 / μm 2 、0.50μm 3 / μm 2 、0.51μm 3 / μm 2 、0.52μm 3 / μm 2 、0.53μm 3 / μm 2 、0.54μm 3 / μm 2 、0.55μm 3 / μm 2 、0.56μm 3 / μm 2 、0.57μm 3 / μm 2 、0.58μm 3 / μm 2 、0.59μm 3 / μm 2 、0.60μm 3 / μm 2 、0.61μm 3 / μm 2 、0.62μm 3 / μm 2 、0.63μm 3 / μm 2 、0.64μm 3 / μm 2 、0.65μm 3 / μm 2 、0.66μm 3 / μm 2 、0.67μm 3 / μm 2 、0.68μm 3 / μm 2 、0.69μm 3 / μm 2 、0.70μm 3 / μm 2 、0.71μm 3 / μm 2 、0.72μm 3 / μm 2 、0.73μm 3 / μm 2 、0.74μm 3 / μm 2 、0.75μm 3 / μm 2 、0.76μm 3 / μm 2 、0.77μm 3 / μm 2 、0.78μm 3 / μm 2 、0.79μm 3 / μm 2 、0.80μm 3 / μm 2 、0.81μm 3 / μm 2 、0.82μm 3 / μm 2 、0.83μm 3 / μm 2 、0.84μm 3 / μm 2 、0.85μm 3 / μm 2 、0.86μm 3 / μm 2 、0.87μm 3 / μm 2 、0.88μm 3 / μm 2 、0.89μm 3 / μm 2 、0.90μm 3 / μm 2 、0.91μm 3 / μm 2 、0.92μm 3 / μm 2 、0.93μm 3 / μm 2 、0.94μm 3 / μm 2 、0.95μm 3 / μm 2 、0.96μm 3 / μm 2 、0.97μm3 / μm 2 、0.98μm 3 / μm 2 、0.99μm 3 / μm 2 , 1.00μm 3 / μm 2 , 1.01μm 3 / μm 2 , 1.02μm 3 / μm 2 , 1.03μm 3 / μm 2 , 1.04μm 3 / μm 2 , 1.05μm 3 / μm 2 , 1.06μm 3 / μm 2 , 1.07μm 3 / μm 2 、1.08μm 3 / μm 2 , 1.09μm 3 / μm 2 , 1.10μm 3 / μm 2 , 1.11μm 3 / μm 2 , 1.12μm 3 / μm 2 , 1.13μm 3 / μm 2 , 1.14μm 3 / μm 2 , 1.15μm 3 / μm 2 , 1.16μm 3 / μm 2 , 1.17μm 3 / μm 2 , 1.18μm 3 / μm 2 , 1.19μm 3 / μm 2 , or 1.20μm 3 / μm 2 , or within the range formed by any two of the above values. Vmp is the volume of the protruding peak of the material at a specific load area ratio. Studies have shown that controlling the Vmp value of the first surface of the polymer film at a load area ratio of 10% within a specified range can avoid severe adhesion between polymer films when stacked and improve the exhaust effect during pre-pressing.
[0029] In addition, the Sku value of the first surface of the polymer film of the present invention is 0.73 to 10.02, for example, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75 , 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.0 0, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30, 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, 4.05, 4.10, 4.15, 4.20, 4.2 5, 4.30, 4.35, 4.40, 4.45, 4.50, 4.55, 4.60, 4.65, 4.70, 4.75, 4.80, 4.85, 4.90, 4.95, 5.00, 5.05, 5.10, 5.15, 5.20, 5.25, 5.30, 5.35, 5.40, 5.45, 5. 50, 5.55, 5.60, 5.65, 5.70, 5.75, 5.80, 5.85, 5.90, 5.95, 6.00, 6.05, 6.10, 6.15, 6.20, 6.25, 6.30, 6.35, 6.40, 6.45, 6.50, 6.55, 6.60, 6.65, 6.70, 6. 75, 6.80, 6.85, 6.90, 6.95, 7.00, 7.05, 7.10, 7.15, 7.20, 7.25, 7.30, 7.35, 7.40, 7.45, 7.50, 7.55, 7.60, 7.65, 7.70, 7.75, 7.80, 7.85, 7.90, 7.95, 8. 00, 8.05, 8.10, 8.15, 8.20, 8.25, 8.30, 8.35, 8.40, 8.45, 8.50, 8.55, 8.60, 8.65, 8.70, 8.75, 8.80, 8.85, 8.90, 8.95, 9.00, 9.05, 9.10, 9.15, 9.20, 9.25, 9.30, 9.35, 9.40, 9.45, 9.50, 9.55, 9.60, 9.65, 9.70, 9.75, 9.80, 9.85, 9.90, 9.95, 10.00, or 10.02, or within a range consisting of any two of the above values. Sku refers to the sharpness of the surface height distribution of the roughness profile. Studies have shown that controlling the Vmp value and Sku value of the first surface within the specified range can avoid severe adhesion of the polymer film when stacked, and can improve the exhaust effect during pre-pressing, so as to obtain a laminated glass without bubble defects and further having excellent weather resistance. .
[0030] In a preferred embodiment of the present invention, the Vmp value of the second surface of the polymer film at a loading area ratio of 10% is 0.15 μm 3 / μm 2 Up to 1.20μm 3 / μm 2 The Sku value of the second surface is 0.73 to 10.02. The specific numerical examples of the Vmp value and the Sku value of the second surface can refer to the relevant description of the first surface, which will not be repeated here.
[0031] In addition, research shows that when the Vmp value is the same, the lower the Sku value, the more serious the stickiness problem of the polymer film. When the Sku value is the same, the higher the Vmp value, the worse the exhaust effect of the polymer film, and the laminated glass produced is prone to bubble defects and poor weather resistance.
[0032] 1.1.2. Average length of contour curve elements (Rsm)
[0033] In addition to the aforementioned parameters, it has been found that the average length (Rsm) of the profile curve elements on the surface of the polymer film can be controlled to further improve the degassing in the pre-pressing process of the laminated glass. In a preferred embodiment of the present invention, the Rsm values of the first surface and the second surface of the polymer film are independently 10 μm to 660 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm, 310 μm, 320 μm, 330 μm, 340 μm, 350 μm, 360 μm, 370 μm, 380 μm, 390 μm, 400 μm, 410 μm, 420 μm, 430 μm, 440 μm, 450 μm, 460 μm, 470 μm, 480 μm, 490 μm, 500 μm, 510 μm, 521 μm, 530 μm, 540 μm, 550 μm, 560 μm, 570 μm, 580 μm, 590 μm, 600 μm, 0 microns, 20 microns, 330 microns, 340 microns, 350 microns, 360 microns, 370 microns, 380 microns, 390 microns, 400 microns, 410 microns, 420 microns, 430 microns, 440 microns, 450 microns, 460 microns, 470 microns, 480 microns, 490 microns, 500 microns, 510 microns, 520 microns, 530 microns, 540 microns, 550 microns, 560 microns, 570 microns, 580 microns, 590 microns, 600 microns, 610 microns, 620 microns, 630 microns, 640 microns, 650 microns, or 660 microns, or in a range consisting of any two of the above values. Studies have shown that if the Rsm value is too low or too high, it will affect the air discharge and may cause bubble defects. Even if the residual air can be dissolved into the polymer film during the positive pressing of the laminated glass (i.e., the air storage phenomenon) without bubble defects, after long-term use or under more severe conditions, the air will still dissolve from the polymer film to form bubbles in the laminated glass. Therefore, the weather resistance of the laminated glass is not good (the results of the "high temperature bubble test" are not good).
[0034] In addition, studies have shown that when the Vmp value and Sku value of the polymer film surface are both within the specified range, if the Rsm value falls within the above specified range, the weather resistance of the laminated glass obtained is better (that is, the "high temperature bubble test" result is better). Therefore, in a preferred embodiment of the present invention, the Vmp value, Sku value and Rsm value of the first surface and the second surface of the polymer film are each independently within the above specified range.
[0035] 1.2. Composition of polymer films
[0036] The polymer film of the present invention comprises polyvinyl acetal as an essential component, and may further comprise other optional components, such as plasticizers or other existing additives, as required. In some embodiments of the present invention, the polymer film comprises polyvinyl acetal and plasticizer, or the polymer film is substantially composed of polyvinyl acetal and plasticizer, or the polymer film is composed of polyvinyl acetal and plasticizer.
[0037] The polymer film of the present invention can be a single-layer film consisting of a single layer, or a multi-layer film consisting of multiple layers, as long as the polymer film as a whole meets the specified Vmp value and Sku value conditions, preferably meets the specified Rsm conditions. In the scheme where the polymer film is a multi-layer film, the materials of each layer of the polymer film can be the same or different, and each plays the same or different functional layer, and the functional layer is, for example, a layer that can provide one or more of the following functions: sound insulation function, heat insulation function, reflection function, anti-reflection function, refraction function, anti-refraction function, light splitting function, and light reduction function.
[0038] 1.2.1. Polyvinyl acetal
[0039] Examples of polyvinyl acetals include, but are not limited to, poly(vinyl formal), poly(vinyl acetal), poly(vinyl butyral), poly(vinyl valeral), and poly(vinyl hexane). Each of the aforementioned polyvinyl acetals may be used alone or in combination. In a preferred embodiment of the present invention, the polyvinyl acetal is poly(vinyl butyral). In the following examples, the polymer film is composed of poly(vinyl butyral) and a plasticizer, and is a "poly(vinyl butyral) film (PVB film)", or may be referred to as a "PVB film containing a plasticizer".
[0040] The molecular weight of polyvinyl acetal is not particularly limited. In some embodiments of the present invention, the number average molecular weight (Mn) of polyvinyl acetal may be 90,000 to 120,000, such as 90,000, 90,500, 91,000, 91,500, 92,000, 92,500, 93,000, 93,500, 94,000, 94,500, 95,000, 95,500, 96, 000、96,500、97,000、97,500、98,000、98,500、99,000、99,500、100,000、100,500、101,000、101,500、102,000、102,500、103,000、103,500、104,000、,104,500、105 ,000、105,500、106,000、106,500、107,000、107,500、108,000、108,500、109,000、109,500、110,000、110,500、111,000、111,500、112,000、112,500、113,000、113, Preferably, the Mn of the polyvinyl acetal is 93,750 to 118,750.
[0041] In some embodiments of the present invention, the acetal group content (i.e., degree of acetalization) of the polyvinyl acetal may be 75 wt % to 85 wt %, for example, 75 wt %, 75.1 wt %, 75.2 wt %, 75.3 wt %, 75.4 wt %, 75.5 wt %, 75.6 wt %, 75.7 wt %, 75.8 wt %, 75.9 wt %, 76 wt %, 76.1 wt %, 76.2 wt %, 76.3 wt %, 76.4 wt %, 76.5 wt %, 76.6 wt %, 76.7 wt %, 76.8 wt %, based on the total weight of the hydroxyl group, acetal group, and acetyl group of the polyvinyl acetal. %, 76.9 wt%, 77 wt%, 77.1 wt%, 77.2 wt%, 77.3 wt%, 77.4 wt%, 77.5 wt%, 77.6 wt%, 77.7 wt%, 77.8 wt%, 77.9 wt%, 78 wt%, 78.1 wt%, 78.2 wt%, 78.3 wt%, 78.4 wt%, 78.5 wt%, 78.6 wt%, 78.7 wt%, 78.8 wt%, 78.9 wt%, 79 wt%, 79.1 wt%, 79.2 wt%, 79.3 wt%, 79.4 wt%, 79.5 wt%, 79.6 wt%, 79.7 wt%, 9.7 wt%, 79.8 wt%, 79.9 wt%, 80 wt%, 80.1 wt%, 80.2 wt%, 80.3 wt%, 80.4 wt%, 80.5 wt%, 80.6 wt%, 80.7 wt%, 80.8 wt%, 80.9 wt%, 81 wt%, 81.1 wt%, 81.2 wt%, 81.3 wt%, 81.4 wt%, 81.5 wt%, 81.6 wt%, 81.7 wt%, 81.8 wt%, 81.9 wt%, 82 wt%, 82.1 wt%, 82.2 wt%, 82.3 wt%, 82.4 wt%, 82 %, 83.1 wt %, 83.2 wt %, 83.3 wt %, 83.4 wt %, 83.5 wt %, 83.6 wt %, 83.7 wt %, 83.8 wt %, 83.9 wt %, 84 wt %, 84.1 wt %, 84.2 wt %, 84.3 wt %, 84.4 wt %, 84.5 wt %, 84.6 wt %, 84.7 wt %, 84.8 wt %, 84.9 wt %, or 85 wt %, or within a range consisting of any two of the above values. Preferably, the acetal content (i.e., degree of acetalization) of the polyvinyl acetal may be 78.4 wt % to 81.5 wt %, based on the total weight of the hydroxyl group, acetal group and acetyl group of the polyvinyl acetal.
[0042] In some embodiments of the present invention, the acetyl content (i.e., degree of acetylation) of the polyvinyl acetal may be 0% by weight to 1.5% by weight, based on the total weight of the hydroxyl group, acetal group, and acetyl group of the polyvinyl acetal, for example, 0%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.7%, 0.8%, 0.9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, %, 0.6 wt %, 0.65 wt %, 0.7 wt %, 0.75 wt %, 0.8 wt %, 0.85 wt %, 0.9 wt %, 0.95 wt %, 1.0 wt %, 1.05 wt %, 1.1 wt %, 1.15 wt %, 1.2 wt %, 1.25 wt %, 1.3 wt %, 1.35 wt %, 1.4 wt %, 1.45 wt %, or 1.5 wt %, or in a range consisting of any two of the above values. Preferably, the acetyl content (i.e., degree of acetylation) of the polyvinyl acetal may be 0.8 wt % to 1.2 wt % based on the total weight of the hydroxyl group, acetal group, and acetyl group of the polyvinyl acetal. If the degree of acetylation of the polyvinyl acetal is higher than the specified range, the polymer film is relatively soft and the embossed pattern is prone to being too deep.
[0043] In some embodiments of the present invention, the hydroxyl content of the polyvinyl acetal may be 15 wt % to 25 wt %, for example, 15 wt %, 15.1 wt %, 15.2 wt %, 15.3 wt %, 15.4 wt %, 15.5 wt %, 15.6 wt %, 15.7 wt %, 15.8 wt %, 15.9 wt %, 16 wt %, 16.1 wt %, 16.2 wt %, 16.3 wt %, 16.4 wt %, 16.5 wt %, 16.6 wt %, 16.7 wt %, 16.8 wt %, 16.9 wt %, based on the total weight of the hydroxyl group, acetal group and acetyl group of the polyvinyl acetal. %, 17.1 wt %, 17.2 wt %, 17.3 wt %, 17.4 wt %, 17.5 wt %, 17.6 wt %, 17.7 wt %, 17.8 wt %, 17.9 wt %, 18 wt %, 18.1 wt %, 18.2 wt %, 18.3 wt %, 18.4 wt %, 18.5 wt %, 18.6 wt %, 18.7 wt %, 18.8 wt %, 18.9 wt %, 19 wt %, 19.1 wt %, 19.2 wt %, 19.3 wt %, 19.4 wt %, 19.5 wt %, 19.6 wt %, 19.7 wt %. %, 19.8 wt%, 19.9 wt%, 20 wt%, 20.1 wt%, 20.2 wt%, 20.3 wt%, 20.4 wt%, 20.5 wt%, 20.6 wt%, 20.7 wt%, 20.8 wt%, 20.9 wt%, 21 wt%, 21.1 wt%, 21.2 wt%, 21.3 wt%, 21.4 wt%, 21.5 wt%, 21.6 wt%, 21.7 wt%, 21.8 wt%, 21.9 wt%, 22 wt%, 22.1 wt%, 22.2 wt%, 22.3 wt%, 22.4 wt%, 22.5 %, 22.6 wt %, 22.7 wt %, 22.8 wt %, 22.9 wt %, 23 wt %, 23.1 wt %, 23.2 wt %, 23.3 wt %, 23.4 wt %, 23.5 wt %, 23.6 wt %, 23.7 wt %, 23.8 wt %, 23.9 wt %, 24 wt %, 24.1 wt %, 24.2 wt %, 24.3 wt %, 24.4 wt %, 24.5 wt %, 24.6 wt %, 24.7 wt %, 24.8 wt %, 24.9 wt %, or 25 wt %, or within a range consisting of any two of the above values. Preferably, the hydroxyl content of the polyvinyl acetal may be 17.5 wt % to 20.6 wt %, based on the total weight of the hydroxyl groups, acetal groups and acetyl groups of the polyvinyl acetal. If the hydroxyl content of the polyvinyl acetal is higher than the specified range, the polymer film is relatively hard and it is not easy to form an embossed pattern.If the hydroxyl content of the polyvinyl acetal is below the specified range, the polymer film is relatively soft and the embossed pattern tends to be too deep.
[0044] 1.2.2 Plasticizer
[0045] Herein, plasticizer refers to a chemical substance that can change the plasticity of thermoplastic resin, and may also be referred to as plasticizer. Examples of plasticizers include, but are not limited to, esters of polyacids or polyols, such as triethylene glycol bis(2-ethylhexanoate), tetraethylene glycol bis(2-ethylhexanoate), triethylene glycol bis(2-ethylbutyrate), tetraethylene glycol bis(2-ethylbutyrate), triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, dihexyl adipate, dioctyl adipate, cyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl sebacate, bis[2-(2-butoxyethoxy)ethyl adipate], polymeric adipate (polymeric adipate), dipropylene glycol dibenzoate, tripropylene glycol dibenzoate, polypropylene glycol dibenzoate, isodecyl benzoate, 2-ethylhexyl benzoate, propylene glycol dibenzoate, diisononyl phthalate, dibutoxyethyl terephthalate, castor oil, methyl ricinoleate, soybean oil, epoxidized soybean oil, and combinations thereof. In the examples attached hereto, triethylene glycol bis(2-ethylhexanoate) is used as a plasticizer.
[0046] There is no particular restriction on the amount of plasticizer, as long as the desired plasticizing effect can be provided. Generally speaking, the amount of plasticizer can be controlled to be 35 to 50 parts by weight based on 100 parts by weight of polyvinyl acetal, such as 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, or 50 parts by weight, or within the range formed by any two of the above values. In some embodiments of the present invention, the amount of plasticizer is 37 to 48 parts by weight. If the amount of plasticizer is higher than the specified range, the polymer film is relatively soft and the embossed pattern is prone to being too deep. If the amount of plasticizer is lower than the specified range, the polymer film is relatively hard and it is not easy to form embossed patterns.
[0047] 1.2.3. Other existing additives
[0048] Existing additives may include any substance that can adaptably improve the processability of the polymer film during the manufacturing process, or impart specific functions to the polymer film. Examples of existing additives include, but are not limited to, dyes, pigments, stabilizers, antioxidants, flame retardants, infrared absorbers, infrared blockers, ultraviolet absorbers, ultraviolet stabilizers, lubricants, dispersants, surfactants, chelating agents, coupling agents, adhesives, and adhesion control agents. The aforementioned additives can be used alone or in combination. For example, the polymer film may contain a dye or a pigment to form a colored polymer film, or contain an ultraviolet absorber or an infrared absorber to form a polymer film with anti-ultraviolet function or a polymer film with anti-infrared function.
[0049] 1.3. Other properties of polymer films
[0050] 1.3.1. Glass transition temperature (Tg)
[0051] In some embodiments of the present invention, the glass transition temperature (Tg) of the polymer film can be controlled within a range of 5°C to 23°C, such as 5°C, 5.5°C, 6°C, 6.5°C, 7°C, 7.5°C, 8°C, 8.5°C, 9°C, 9.5°C, 10°C, 10.5°C, 11°C, 11.5°C, 12°C, 12.5°C, 13°C, 13.5°C, 14°C, 14.5°C, 15°C, 15.5°C, 16°C, 16.5°C, 17°C, 17.5°C, 18°C, 18.5°C, 19°C, 19.5°C, 20°C, 20.5°C, 21°C, 21.5°C, 22°C, 22.5°C, or 23°C, or within a range formed by any two of the above values. If the Tg of the polymer film is higher than the specified range, the polymer film is relatively hard, and it may be difficult to form the desired texture when mechanical embossing is performed. If the Tg of the polymer film is lower than the specified range, the polymer film is relatively soft, and the embossing pattern formed during mechanical embossing is likely to be too deep. According to the present invention, the Tg of the polymer film is preferably 6°C to 22.5°C, more preferably 10°C to 22.5°C.
[0052] 1.3.2.Thickness
[0053] Under the condition of meeting the specified Vmp value and Sku value, the polymer film of the present invention can have a uniform thickness and the thickness can be adjusted according to actual needs. Generally speaking, the thickness of the polymer film can be 0.1 mm to 2.5 mm, such as 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm, 1.0 mm, 1.05 mm, 1.1 mm, 1.15 mm, 1.2 mm, 1.25 mm In some embodiments, the polymer film has a thickness of 0.1 mm, 0.2 mm, 0.3 mm, 0.76 mm, or 1.52 mm. In some embodiments, the polymer film has a thickness of 0.1 mm, 0.2 mm, 0.3 mm, 0.76 mm, or 1.52 mm.
[0054] The polymer film of the present invention may also be a wedge-shaped film with different thicknesses at both ends, which is usually used to prepare a head-up display (HUD) for a car, and is therefore also referred to as a "HUD film" herein. In some embodiments of the present invention, the thickness of the thin end of the HUD film may be 0.5 to 1 mm, such as 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm, or 1 mm, or in a range consisting of any two of the above values. In some embodiments of the present invention, the thickness of the thick end of the HUD film may be 1.2 mm to 1.7 mm, such as 1.2 mm, 1.25 mm, 1.3 mm, 1.35 mm, 1.4 mm, 1.45 mm, 1.5 mm, 1.55 mm, 1.6 mm, 1.65 mm, or 1.7 mm, or in a range consisting of any two of the above values. In the following embodiments, the thickness of the thin end of the HUD film is 0.76 mm and the thickness of the thick end is 1.45 mm, and the width of the HUD film is about 1200 mm.
[0055] 1.4. Preparation of polymer membranes
[0056] The preparation method of the polymer film of the present invention is not particularly limited. For example, polyvinyl acetal and selected components (such as plasticizers) can be mixed and kneaded to obtain a polymer film composition, and then the polymer film composition is formed into a film using an existing film preparation method, and mechanical embossing is performed to facilitate providing the desired Vmp, Sku and Rsm on the surface of the polymer film. Examples of the film preparation method include, but are not limited to, calendaring, casting, extrusion tentering, direct extrusion, and extrusion blow molding.
[0057] In some embodiments of the present invention, a polymer film with uniform thickness is prepared in the following manner, but the present invention is not limited thereto: a resinous polyvinyl acetal (e.g., PVB) and a plasticizer are mixed at a temperature of 100° C. to 150° C. and a rotation speed of 10 rpm to 50 rpm using a mixer, and kneaded for 5 minutes to 30 minutes to obtain a polymer film composition. After the polymer film composition is cooled to room temperature, the polymer film composition is placed in an extruder and extruded into a polymer film (PVB film). In addition, the above film-forming steps can be repeated as needed and the composition of the polymer film composition can be adjusted to provide films with different functions, and the films can be laminated to form a polymer film with a multilayer structure.
[0058] In some embodiments of the present invention, the HUD film is prepared in the following manner, but the present invention is not limited thereto: a resin-state polyvinyl acetal (such as PVB) and a plasticizer are mixed at a temperature of 100° C. to 150° C. and a rotation speed of 10 rpm to 50 rpm using a mixer, and kneaded for 5 minutes to 30 minutes to obtain a polymer film composition. After the polymer film composition is cooled to room temperature, the polymer film composition is placed in an extruder to extrude a polymer film (PVB film), wherein the outlet of the extruder is set to a wedge shape, so that the extruded polymer film has two ends with different thicknesses (i.e., a thick end and a thin end).
[0059] The polymer film can then be preheated and mechanically embossed to provide the desired Vmp, Sku and, if necessary, Rsm. Mechanical embossing refers to the use of a roller to create textures on the surface of the formed polymer film. The methods of mechanical embossing include, but are not limited to, an embossing wheel method and a calendering wheel method, of which the embossing wheel method is preferred. There are no special restrictions on the pattern of mechanical embossing, including, for example, diamond, linear, serrated, square, conical, circular, approximately circular, and irregular shapes. The aforementioned pattern styles can be used alone or in combination.
[0060] Regarding the Vmp, Sku and Rsm properties of the polymer film, the study found that the Vmp, Sku and Rsm of the polymer film can be adjusted by controlling the diameter and rotation speed of the embossing wheel. Generally speaking, the contact area between the polymer film surface and the embossing wheel is usually 1 / 3 of the circumference of the embossing wheel. The larger the diameter of the embossing wheel, the larger the circumference of the embossing wheel, and the larger the contact area between the polymer film surface and the embossing wheel, so that the polymer film is subjected to heat pressing for a longer time, and the embossing pattern on the surface is deeper (sharper). On the contrary, the smaller the diameter of the embossing wheel, the shallower (coarse and blunt) the embossing pattern on the surface of the polymer film. Furthermore, if the rotation speed of the embossing wheel is higher, the moving speed of the polymer film is faster, so that the polymer film is subjected to heat pressing for a shorter time, the embossing pattern on the surface is shallower and uneven, and the distance between the patterns is also shorter, so the Rsm is lower. On the contrary, if the embossing wheel speed is low, the moving speed of the polymer film is slow, so that the polymer film is subjected to heat pressing for a longer time, the embossing patterns on the surface are deeper and more uniform, and the distance between the patterns is also longer, so the Rsm is higher. Therefore, when making the polymer film of the present invention, the Vmp value and Sku value of the polymer film surface can be increased or decreased by adjusting the embossing wheel diameter and the embossing wheel speed in coordination, thereby obtaining a polymer film having the Vmp and Sku technical characteristics of the present invention.
[0061] 2. Laminated glass
[0062] The polymer film of the present invention can be used to prepare laminated glass. Therefore, the present invention also provides a laminated glass, which comprises a first glass sheet, a second glass sheet, and an intermediate film located between the first glass sheet and the second glass sheet, wherein the intermediate film is provided by the polymer film as described above.
[0063] The first glass sheet and the second glass sheet may be the same or different, and may be any glass sheet currently used to prepare laminated glass, such as float glass, tempered glass, wired glass, or ordinary flat glass, but the present invention is not limited thereto. In the following embodiments, float glass is used as the first glass sheet and the second glass sheet.
[0064] The laminated glass of the present invention can be prepared by the existing laminated glass preparation method in the related technical field. For example, the laminated glass can be prepared as follows: a polymer film is sandwiched between two glass sheets to obtain a laminated object. The laminated glass of the present invention can be prepared by the existing laminated glass preparation method in the related technical field. For example, the laminated glass can be prepared as follows: a polymer film is sandwiched between two glass sheets to obtain a laminated object, the laminated object is placed in a vacuum bag and evacuated at a temperature of 20°C to 30°C (vacuum degree>500mmHg (millimeters of mercury), such as 700mmHg) for at least 10 minutes, then the vacuum bag containing the laminated object is placed in a heating furnace, and the temperature is slowly raised from 60°C to 140°C. After at least 40 minutes, the vacuum bag is taken out of the heating furnace to complete pre-pressing. Then, the pre-pressed laminated object is placed in an autoclave for positive pressing, and hot-pressed for 100 minutes to 150 minutes under high temperature and high pressure conditions to obtain laminated glass. Generally speaking, the high temperature and high pressure conditions may be a pressure of 10 bar to 15 bar and a temperature of 100° C. to 150° C.
[0065] 3. Example
[0066] 3.1. Description of measurement method
[0067] The present invention is further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:
[0068] [Measurement of Molecular Weight of Polyvinyl Acetal]
[0069] The molecular weight distribution of polyvinyl acetal was measured by gel permeation chromatography (GPC), wherein polyvinyl acetal was dissolved in tetrahydrofuran (THF), GPC analysis was performed under the following conditions, and the molecular weight was calculated as the ratio of the area corresponding to the polystyrene standard (Waters PS STD).
[0070] Device: Waters 1515PUMP system
[0071] Detector: Waters 2414RI
[0072] Elution conditions: 1.0 mL / min, THF
[0073] Column: Waters Styragel HR5 THF, Waters Styragel HR4 THF, Waters StyragelHR3 THF, Waters Styragel HR1 THF
[0074] [Measurement of acetal degree, acetylation degree and hydroxyl content of polyvinyl acetal]
[0075] The acetalization degree, acetylation degree and hydroxyl content of polyvinyl acetal are measured in accordance with JIS K6728.
[0076] [Measurement of glass transition temperature (Tg)]
[0077] The Tg of the polymer film was measured in a nitrogen atmosphere using a differential scanning calorimeter (model: TA DSC 25, purchased from TA Instruments). First, 7 mg of the polymer film was taken as a sample and placed on the sample stage of the differential scanning calorimeter, and the temperature was raised to 150°C at a heating rate of 10°C / min and then maintained at this temperature for 5 minutes. Then, the sample was equilibrated at -50°C and maintained at this temperature for 5 minutes, and then the temperature was raised to 100°C at a heating rate of 10°C / min to obtain a temperature versus heat flow curve (X axis is temperature, Y axis is heat flow), and the temperature corresponding to the midpoint of the glass transition was recorded as Tg.
[0078] [Measurement of Vmp and Sku]
[0079] First, a 30 cm × 30 cm polymer film was taken, and a 3 cm × 3 cm test sample was cut from each of the four corners of the polymer film at a distance of 1 cm from the edge, and a 3 cm × 3 cm test sample was cut from the center of the polymer film, obtaining a total of five test samples. Then, at a temperature of 24±3°C and a relative humidity of 63±3%, according to the specification of ISO25178-2:2012, a laser scanning confocal microscope (model: LEXT OLS5000-SAF, purchased from Olympus) was used to measure the Vmp value and Sku value of the test sample at a load area rate of 10%. The measurement conditions are as follows: the light source has a wavelength of 405 nanometers, the objective lens magnification is 100 times (MPLAPON-100xLEXT), the optical zoom is 50 times, the image area is 1500 microns × 1500 microns, the resolution is 1024 pixels × 1024 pixels, the operating conditions are set to auto tilt removal, and no filter is used.
[0080] In the obtained load area curve, the Vmp value at a load area ratio of 10% can be obtained, and its unit is μm 3 / μm 2In addition, the Sku value can be obtained through program calculation. In the following examples, the Vmp value is obtained by averaging five Vmp values from five test samples, and the Sku value is obtained by averaging five Sku values from five test samples.
[0081] [Measurement of Rsm]
[0082] First, a 30 cm × 30 cm polymer film is taken, and a 3 cm × 3 cm test sample is cut at 1 cm from each of the four corners of the polymer film, and a 3 cm × 3 cm test sample is cut at the center of the polymer film, to obtain a total of five test samples. Next, the Rsm value of the test sample of the polymer film is measured using a laser scanning conjugate focus microscope at a temperature of 24±3°C and a relative humidity of 63±3% according to the specification of ISO 4287:1997. The measurement conditions are as follows: the light source has a wavelength of 405 nm, the objective lens magnification is 100 times, the optical zoom is 50 times, the image area is 1500 μm × 1500 μm, the resolution is 1024 pixels × 1024 pixels, and the operating condition is set to automatic tilt removal without using a filter. In the attached examples, the Rsm value is calculated based on the average of the five Rsm values from the five test samples.
[0083] [Evaluation of residual bubbles]
[0084] After the laminated glass was prepared, the remaining bubbles were evaluated by naked eyes immediately. The part with the shortest distance of 15 mm from the edge of the glass, where bubbles were particularly likely to appear, was observed and evaluated according to the following standards.
[0085] ◎: No bubbles appear
[0086] ○: A bubble appears
[0087] ×: Two or more bubbles appear
[0088] [High temperature bubble residue test]
[0089] The laminated glass was cut into test samples of 30 cm x 30 cm. The test samples were placed vertically in a 120°C oven for 2 hours, then taken out and observed with the naked eye for the part of the test sample where bubbles were particularly likely to appear and the shortest distance from the glass edge was less than 15 mm, and evaluated according to the following standards.
[0090] ◎: No bubbles appear
[0091] ○: A bubble appears
[0092] ×: Two or more bubbles appear
[0093] [Self-adhesion test]
[0094] First, cut the polymer film into test samples of 10 cm x 2 cm. Then, while reserving a 2 cm x 2 cm unbonded area as a clamping area, bond the two test samples to obtain a bonded sample. At a temperature of 25°C, press the bonded sample with a weight of 10 kg (without pressing the clamping area) for 30 minutes. Afterwards, use a tensile testing machine (model: AI-7000M, purchased from GOTECH) to clamp the clamping area of the bonded sample and pull apart the two polymer films that make up the bonded sample at a speed of 2 cm / min (centimeter / minute) or 1 cm / min. If the two polymer films are obviously sticky to each other, reduce the speed of the tensile testing machine as needed to increase the force-bearing time. The self-adhesion of the polymer film is evaluated according to the following standards.
[0095] A: The sample can be pulled apart at a speed of 2cm / min, and the two polymer films are not sticky to each other.
[0096] B: The sample can be pulled apart at a speed of 1 cm / min, and the two polymer films are not sticky to each other.
[0097] C: The laminated sample cannot be pulled apart
[0098] 3.2. Preparation and property measurement of polymer films
[0099] First, 100 parts by weight of poly(vinyl butyral) (PVB, purchased from Changchun Petrochemical Co., Ltd.) is mixed with a plasticizer (triethylene glycol bis(2-ethylhexanoate)) in an amount shown in Tables 1-1 and 1-2 to obtain a mixture, and the mixture is kneaded at 120°C at a rotation speed of 35 rpm for 15 minutes using a mixer, and then cooled to room temperature to obtain a polymer film composition. Next, the polymer film composition is placed in an extruder and extruded into a polymer film. The thickness of the polymer film is shown in Tables 1-1 and 1-2. The Mn, acetal degree, acetylation degree and hydroxyl content ratio of the PVB used, and the Tg of the obtained polymer film are measured according to the method described above, and the results are recorded in Tables 1-1 and 1-2. The units of acetal degree, acetylation degree and hydroxyl content ratio are all weight %.
[0100] According to the parameter conditions shown in Table 2-1 and Table 2-2, the two surfaces of the polymer film were preheated and mechanically embossed to obtain the polymer films of Examples 1 to 11 and Comparative Examples 1 to 7. In addition to the parameter conditions shown in Table 2-1 and Table 2-2, the line speed of the polymer film passing between the embossing wheels was 18 m / min (meters / minute). The Vmp, Sku and Rsm of the polymer films of Examples 1 to 11 and Comparative Examples 1 to 7 were measured according to the method described above, and the results are recorded in Table 2-1 to Table 2-2.
[0101] Table 1-1: Properties of polymer films of Examples 1 to 11
[0102]
[0103]
[0104] Table 1-2: Properties of polymer films of Comparative Examples 1 to 7
[0105]
[0106] Table 2-1: Mechanical embossing parameters and properties of polymer films of Examples 1 to 11
[0107]
[0108] Table 2-2: Mechanical embossing parameters and properties of polymer films of Comparative Examples 1 to 7
[0109]
[0110] 3.3. Preparation and property evaluation of laminated glass
[0111] The polymer films of Examples 1 to 11 and Comparative Examples 1 to 7 were used to prepare laminated glass. First, the polymer film was cut into a size of 300 mm × 300 mm. Next, two clean transparent float glass sheets (length 300 mm, width 300 mm, thickness 2 mm) were prepared, and the cut polymer film was sandwiched between the two transparent float glass sheets to obtain a laminate, and the laminate was evacuated using a vacuum bag method for pre-compression. The laminate was placed in a vacuum bag and maintained at a vacuum degree of 700 mmHg at a temperature of 30°C for 10 minutes, and then the vacuum bag containing the laminate was placed in a heating furnace and maintained at a temperature of 140°C for 40 minutes, and then the vacuum bag was taken out of the heating furnace and cooled at room temperature. After cooling, the vacuum was released and the laminate was taken out. The pre-compressed laminate was placed in an autoclave at a pressure of 13 bar and a temperature of 135°C for 120 minutes, and then cooled to room temperature to obtain a laminated glass.
[0112] According to the above methods, the polymer films and laminated glasses of Examples 1 to 11 and Comparative Examples 1 to 7 were subjected to self-adhesion test, bubble residue evaluation, and high-temperature bubble residue test, and the results are recorded in Tables 3-1 and 3-2.
[0113] Table 3-1: Evaluation results of laminated glasses made of polymer films of Examples 1 to 11
[0114]
[0115] Table 3-2: Evaluation results of laminated glasses made of polymer films of Comparative Examples 1 to 7
[0116]
[0117] As shown in Table 3-1, Examples 1 to 9 show that when the Vmp and Sku of the polymer film are within the specified range, the polymer film of the present invention can obtain satisfactory results in the self-adhesion test, and will not affect the smoothness of the process in the laminated glass process. At the same time, the laminated glass prepared from the polymer film of the present invention has no bubble defects after preparation, and can obtain satisfactory results in the high-temperature bubble test, indicating that the laminated glass has good weather resistance. Examples 10 and 11 show that when the Vmp and Sku of the polymer film are within the specified range but the Rsm is not within the specified range, although the polymer film can obtain satisfactory results in the self-adhesion test and has no bubble defects, the laminated glass cannot obtain satisfactory results in the high-temperature bubble test and has poor weather resistance.
[0118] In contrast, as shown in Table 3-2, the polymer film that does not belong to the present invention cannot obtain satisfactory results in the self-adhesion test, which will affect the smoothness of the process in the laminated glass process. Comparative Examples 1 to 4 show that when the Vmp, Sku and Rsm of the polymer film are all outside the specified range, the polymer films are easy to stick to each other and affect the smoothness of the process. Although the laminated glass prepared has no bubble defects after preparation, the laminated glass cannot obtain satisfactory results in the high-temperature bubble test and has poor weather resistance. Comparative Examples 5 and 6 show that when the Vmp of the polymer film falls outside the specified range, even if Sku and Rsm fall within the specified range, satisfactory results cannot be obtained in the self-adhesion test. Comparative Example 7 shows that when the Sku of the polymer film falls outside the specified range, even if Vmp and Rsm fall within the specified range, satisfactory results cannot be obtained in the self-adhesion test.
[0119] The above embodiments are only used to illustrate the principle and efficacy of the present invention and to describe the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily completed by a person skilled in the art without violating the technical principle of the present invention are within the scope of the present invention.
Claims
1. A polymer film, comprising polyvinyl acetal and a plasticizer, wherein the polymer film has a first surface and a second surface, wherein: The first surface has a load area ratio of 0.15 μm at 10%. 3 / µm 2 Up to 1.20 µm 3 / µm 2 and a peak solid volume of 0.73 to 10.02, wherein the load area ratio, peak solid volume and kurtosis are defined in accordance with ISO 25178-2:2012.
2. The polymer film according to claim 1, characterized in that The second surface has a load area ratio of 0.15 μm at 10%. 3 / µm 2 Up to 1.20 µm 3 / µm 2 and a peak solid volume of 0.73 to 10.02, wherein the load area ratio, peak solid volume and kurtosis are defined in accordance with ISO 25178-2:2012.
3. The polymer film according to claim 1, characterized in that The first surface and the second surface each independently have an average length of profile curve elements of 10 micrometers to 660 micrometers, wherein the average length of the profile curve elements is defined according to ISO 4287:1997.
4. The polymer film according to claim 2, characterized in that The first surface and the second surface each independently have an average length of profile curve elements of 10 micrometers to 660 micrometers, wherein the average length of the profile curve elements is defined according to ISO 4287:1997.
5. The polymer film according to claim 1, characterized in that The polymer film has a glass transition temperature of 5°C to 23°C.
6. The polymer film according to claim 2, characterized in that The polymer film has a glass transition temperature of 5°C to 23°C.
7. The polymer film according to claim 1, characterized in that The polyvinyl acetal is poly(vinyl butyral).
8. The polymer film according to claim 2, characterized in that The polyvinyl acetal is poly(vinyl butyral).
9. The polymer film according to claim 1, characterized in that The number average molecular weight of the polyvinyl acetal is 90,000 to 120,000.
10. The polymer film according to claim 2, characterized in that The number average molecular weight of the polyvinyl acetal is 90,000 to 120,000.
11. The polymer film according to claim 1, characterized in that Based on 100 parts by weight of the polyvinyl acetal, the content of the plasticizer is 35 parts by weight to 50 parts by weight.
12. The polymer film according to claim 2, characterized in that Based on 100 parts by weight of the polyvinyl acetal, the content of the plasticizer is 35 parts by weight to 50 parts by weight.
13. A laminated glass, characterized in that: The invention comprises a first glass sheet, a second glass sheet, and an intermediate film located between the first glass sheet and the second glass sheet, wherein the intermediate film is provided by the polymer film as claimed in claim 1.
14. A laminated glass, characterized in that: The invention comprises a first glass sheet, a second glass sheet, and an intermediate film located between the first glass sheet and the second glass sheet, wherein the intermediate film is provided by the polymer film as claimed in claim 2.
Citation Information
Patent Citations
Polymer film and application thereof
CN112876706A
Laminating film, and light-transmitting laminate including same
CN113631384A